The effects of surface roughness on fully developed trans TRANSITIONAL FLOW FRICTION FACTORS IN HORIZONTAL CIRCULAR TUBES - Everts, Marilize (University of Pretoria, 2022)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2022.